Pengembangan e-LKPD Berbasis Project Based Learning untuk Meningkatkan Hasil Belajar Siswa pada Pembelajaran Fiqih - Agam Alfarizi, Aburizal; M.Nur, Azhar; Ninoersy, Tarmizi (Master's degree Department of Islamic Education Postgraduate Program of Universitas Islam Negeri (State Islamic University) Ar-Raniry, Banda Aceh in cooperation with Center for Research and Community Service (LP2M), 2024)
The Purpose of this research is to enhance student learning outcomes on fiqh lesson by creating an electronic learning product namely a Developing electronic Students' Worksheet Based on Project Based Learning ( e-LKPD). Research and Development (R&D) utilizing the ADDIE Learning Statistics data analysis methodologies implemented in this research are the result of a product developed by reserchers and validated by material specialistis and media professionals. The sample that used by researeher was the class of VIII-3 which a mounted to 26 students. Validation result from media experts with an average score of 0,95 and material experts with an average score 0,97 indicate that credible project based e-LKPD in utilized in learning, according to research findings. Following the implementation of e-LKPD in learning, the percentage of students learning outcomes increased to 84,61% from 53,84% the educational result of students can be improved, which makes the application of e-LKPD in education an affective method.